Transformation products of emerging contaminants in the environment : analysis, processes, occurrence, effects and risks - Nollet, Leo M. L., 1948-; Lambropoulou, Dimitra A. (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2014)
Over the last 15 years, the focus of chemical pollution has shifted from conventional pollutants to so-called "emerging" or "new" unregulated contaminants. These include pharmaceuticals and personal care products, hormones, UV filters, perfluorinated compounds, poylybrominated flame retardants (BFRs), pesticides, plasticizers, artificial sweeteners, illicit drugs, and endocrine disruptor compounds (EDCs). Despite the increasing number of published studies covering emerging contaminants, we know almost nothing about the effects of their transformation products and/or metabolites. This two-volume set provides a unique collection of research on transformation products, their occurrence, fate and risks in the environment. It contains 32 chapters, organised into 7 parts, each with a distinct focus: General Considerations Transformation Processes and Treatment Strategies Analytical Strategies Occurrence, Fate and Effects in the Environment Global Speciality and Environmental Status Risk Assessment, Management and Regulatory Framework Outlook Transformation Products of Emerging Contaminants in the Environment is a valuable resource for researchers and industry professionals in environmental chemistry, analytical chemistry, ecotoxicology, environmental sciences, and hydrology, as well as environmental consultants and regulatory bodies.
Part I. General considerations -- part II. Transformation processes and treatment strategies -- part III. Analytical strategies -- part IV. Occurrence, fate and effects in the environment: an overview of major classes -- part V. Global spaciality and environment status of transformation products in the environment -- part VI. Risk assessment, management and regulatory framework -- part VII. Outlook.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Pollution; Speciation (Chemistry); Pollutants -- Biodegradation; Environmental chemistry; Chemicals -- Environmental aspects; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Environmental chemistry; Pollutants -- Biodegradation; Pollution; Speciation (Chemistry); Electronic books